ISOLATION OF CRYPTOCOCCUS NEOFORMANS SPECIES FROM HONEYBEE COLONIES IN MAU FOREST, KENYA - Kipyegon, Kemoi Edson; Kariuki, Stephen Mwaura; Musyoki, Stanslaus Kiilu; Ngetich, Alex Kibet (European Scientific Journal, ESJ, 2015)
Cryptococcus neoformans is an opportunistic pathogen causing infections mainly in immunosupressed individuals. The objective of the study was to evaluate the presence of Cryptococcus species in Mau forest. A total of forty five samples were collected by removing the upper lids of the hive and rubbing the inner surfaces of the beehives with a swab soaked in 0.9% NaCl. The samples were cultured in the Niger seed agar containing 0.1% biphenyl media and incubated at 30°C then observed daily for 15 days. Yeasts producing brownish colouration were further tested for urease activity, cycloheximide resistance and carbohydrate assimilation. Yeasts identifications were done by Canavanine-glycine-bromothymol and API 32C. Serotypes confirmations were done using Crypto check system. A total for two Cryptococcus neoformans species were isolated: Cryptococcus neoformans var. grubii and Cryptococcus neoformans var. gattii. The study found that bee’s act has porters and an indicator, of the presence of Cryptococcus plant flora in the vicinity.